Differential expression and correlation of immunoregulation related piRNA in rheumatoid arthritis - Ren, Ruyu; Tan, Huiling; Huang, Zhuochun; Wang, Yuanyi; Yang, Bin (Frontiers in Immunology, 2023)
(Background) Although PIWI-interacting RNAs (piRNAs) have recently been associated with germline development and many human diseases, their expression pattern and relationship in autoimmune diseases remain indistinct. This study aimed to investigate the presence and correlation of piRNAs in rheumatoid arthritis (RA). (Methods) We first analyzed the expression profile of piRNAs using small RNA sequencing in peripheral leukocytes of three new-onset untreated RA patients and three healthy controls (HCs). We then selected piRNAs related to immunoregulation by bioinformatics analysis and verified them in 42 new-onset RA patients and 81 HCs by RT-qPCR. Furthermore, the receiver operating characteristic curve was generated to quantify the diagnostic performance of these piRNAs. Correlation analysis was conducted to observe the link between piRNAs expression and RA clinical characteristics. (Results) A total of 15 upregulated and 9 downregulated piRNAs among 1565 known piRNAs were identified in peripheral leukocytes of RA patients. Dysregulated piRNAs were enriched in numerous pathways related to immunity. After selection and validation, two immunoregulation piRNAs (piR-hsa-27620 and piR-hsa-27124) were significantly elevated in RA patients and have good abilities to distinguish patients from controls, which have the potential to serve as biomarkers. PIWI and other proteins implicated in the piRNA pathway were also associated with RA.